Some Issues of the Methodology of Diagnosing the Mental Development of Preschool Children - Nematova Nodira Rustamova (Researchparks Publishing, 2022)
This article describes the specific features of psychodiagnostics of the mental development of preschool children, the main purpose of psychological and pedagogical diagnostics, the use and procedure of using methods used in psychological diagnosis of preschool children.